RENEWED TRENDS IN HIGHER EDUCATION FOLLOWING COVID-19 - Vindača, Olga; Ļubkina, Velta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The world in general and the organizations in particular has been changed significantly because of Covid-19 pandemic. The higher education institutions haven’t been an exception. The new challenge has triggered a worldwide shift towards online learning and teaching. There is a question of whether the current situation will lead to the overall transformation of higher education institutions to online, digital or blended one. This paper presents the systematic review of official reports where the new trends concept is used in higher education context. The primary goal of this paper is to establish understanding of already listed trends and directions and to contribute to the discussion of a digital transformation of higher education institutions following Covid-19 pandemic for effective teaching and learning. The paper is based on the theoretical research, including literature and official reports review in the context of transformation of higher education following Covid-19. As primary results, the list of new trends in higher education has been made for effective learning and teaching. This study will help higher education institutions to rethink their strategies according to the necessities to respond to the challenges of such rapid digital transformation.